(untitled) (Costa Rican Journal of Guidance & Counseling, 2022)
The purpose of this document is to share the systematization made to the process of organization, development, and execution of the Techniques and Instruments for Vocational Guidance (TIOV) course, taught at the III level of the Guidance Career at the National University of Costa Rica, during the period from February 11 to June 20, 2019. The proposed objectives were to identify the various theoretical and practical stages of the learning strategies applied in the course, and to promote actions to improve Vocational Guidance courses I, II and, III from the experiences obtained in the development of the methodological strategies of the TIOV course. To achieve this, the methodological process defined by the program of the Alforja Center for Studies and Publications was applied, under the guidance of the General Director, Dr. Oscar Jara Holliday. Regarding the materials to be systematized, the final report of the course, the records identified in the virtual classroom, the teacher files with content and weekly monitoring, the course schedule and the program were reviewed. In addition, an instrument was applied to collect information about some of the experiences and opinions from five students who were in the process, and from the teacher who teaches the same course to another group. Finally, photographs of the events, physical and digital materials prepared by the student body were collected. From which the main conclusions and recommendations for improvement described in this document were reached.